Leukocyte metabolism in obese type 2 diabetic individuals associated with COVID-19 severity - Lobato, Tiago Bertola; Gennari-Felipe, Matheus; Pauferro, Janaína Ribeiro Barbosa; Correa, Ilana Souza; Santos, Beatriz Ferreira; Dias, Beatriz Belmiro; de Oliveira Borges, João Carlos; dos Santos, Camila Soares; de Sousa Santos, Elvirah Samantha; de Araújo, Maria Janaína Leite; Ferreira, Liliane Araújo; Pereira, Sara Araujo; et al. (Frontiers in Microbiology, 2022)
Recent studies show that the metabolic characteristics of different leukocytes, such as, lymphocytes, neutrophils, and macrophages, undergo changes both in the face of infection with SARS-CoV-2 and in obesity and type 2 diabetes mellitus (DM2) condition. Thus, the objective of this review is to establish a correlation between the metabolic changes caused in leukocytes in DM2 and obesity that may favor a worse prognosis during SARS-Cov-2 infection. Chronic inflammation and hyperglycemia, specific and usual characteristics of obesity and DM2, contributes for the SARS-CoV-2 replication and metabolic disturbances in different leukocytes, favoring the proinflammatory response of these cells. Thus, obesity and DM2 are important risk factors for pro-inflammatory response and metabolic dysregulation that can favor the occurrence of the cytokine storm, implicated in the severity and high mortality risk of the COVID-19 in these patients.